Influence of mycorrhization on physiological parameters of micropropagated Castanea sativa Mill. plants - Martins, Anabela (2011)
Mycorrhizal micropropagated Castanea sativa plants were studied in terms of growth and physiological parameters following in vitro mycorrhization with Pisolithus tinctorius. Mycorrhization enhanced growth of micropropagated chestnut plants, increased their protein content and photosynthetic rates, decreased the respiratory rates and CO2 compensation point. RuBisCO activity was not significantly different in mycorrhizal and control plants, although there was an increase in the amount of RuBisCO in the former. Mycorrhization increased plant biomass and improved plants physiological status, thus enhancing the acclimatization process.